2022
DOI: 10.1159/000524962
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approaches to Combatting Childhood Obesity

Abstract: <b>Background:</b> The global prevalence of childhood obesity has grown sharply in recent decades. Obesity is considered a public health problem which directly affects the health status of children in numerous ways. To combat this trend, integrated approaches are necessary to prevent childhood obesity. Strategies require a comprehensive perspective at individual and parental level alongside the adoption of measures to engage the community and environment. <b><i>Summary:</i></b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 73 publications
(122 reference statements)
0
19
0
2
Order By: Relevance
“…Healthy Eating (HEI) study observed that obesity in adolescents correlated with diet quality [ 14 ]. Additionally, skipping breakfast is a critical risk factor for obesity development, as several studies reported a significant association between skipping breakfast and the risk of adiposity [ 15 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Healthy Eating (HEI) study observed that obesity in adolescents correlated with diet quality [ 14 ]. Additionally, skipping breakfast is a critical risk factor for obesity development, as several studies reported a significant association between skipping breakfast and the risk of adiposity [ 15 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…They combine this with a plethora of energysaving devices, mechanization of the workplace, and the temptations of sedentary past times, and it is little wonder that the world has got fatter. In 2019, the World Health Organization (WHO) estimated that 38 million children under 5 years worldwide were overweight or obese; almost half of whom live in Asia In their paper "Integrated Approaches to Combatting Childhood Obesity," Elvira Verducia and colleagues discuss the individual components of the obesogenic environment of the Anthropocene [4]. They make individual recommendations for tackling each aspect but, in common with other commentators, stress that progress against obesity will not be achieved without adopting integrated approaches to simultaneously tackle all (or at least most) of the contributory drivers.…”
Section: Doi: 101159/000524128mentioning
confidence: 99%
“…In their paper “Integrated Approaches to Combatting Childhood Obesity,” Elvira Verducia and colleagues discuss the individual components of the obesogenic environment of the Anthropocene [4]. They make individual recommendations for tackling each aspect but, in common with other commentators, stress that progress against obesity will not be achieved without adopting integrated approaches to simultaneously tackle all (or at least most) of the contributory drivers.…”
mentioning
confidence: 99%
“…Additionally, childhood obesity is associated with increased risk of adult obesity, which is related to poor health throughout adulthood and increased premature mortality [2]. Numerous modifiable factors increase obesity risk, including inadequate intake of fruits/vegetables, irregular breakfast consumption, excessive intake of sugarsweetened beverages, limited physical activity, frequent sedentary activity, and inadequate sleep duration [3][4][5][6][7][8] Parents play a pivotal role in mitigating obesity risk for children [9,10]. Parents primarily influence their children's behaviors through role modeling and reinforcement of healthy behaviors [9,10].…”
Section: Introductionmentioning
confidence: 99%